Spearman correlation analysis between gut microbial taxa and circulating metabolites, detailing correlation coefficients, significance values, and taxon–metabolite pairings indicative of microbiome–host metabolic interactions. - Ji-Xin Zhao (22056386) (2025)
Spearman correlation analysis between gut microbial taxa and circulating metabolites, detailing correlation coefficients, significance values, and taxon–metabolite pairings indicative of microbiome–host metabolic interactions.